2021
DOI: 10.3310/hta25350
|View full text |Cite
|
Sign up to set email alerts
|

Modelling tool to support decision-making in the NHS Health Check programme: workshops, systematic review and co-production with users

Abstract: Background Local authorities in England commission the NHS Health Check programme to invite everyone aged 40–74 years without pre-existing conditions for risk assessment and eventual intervention, if needed. However, the programme’s effectiveness, cost-effectiveness and equity impact remain uncertain. Aim To develop a validated open-access flexible web-based model that enables local commissioners to quantify the cost-effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 186 publications
(414 reference statements)
0
6
0
Order By: Relevance
“…In the UK, a large CVD risk detection and management programme, including substantial efforts to detect and control hypertension, seems to reduce the burden but is highly dependent on how ‘optimised’ the programme is, including maximising uptake and compliance with the interventions. This is essential and more so if the goal is also to reduce health inequalities or reach disadvantaged groups 13…”
Section: What Are the Challenges?mentioning
confidence: 99%
“…In the UK, a large CVD risk detection and management programme, including substantial efforts to detect and control hypertension, seems to reduce the burden but is highly dependent on how ‘optimised’ the programme is, including maximising uptake and compliance with the interventions. This is essential and more so if the goal is also to reduce health inequalities or reach disadvantaged groups 13…”
Section: What Are the Challenges?mentioning
confidence: 99%
“…Critically, equal partnership requires compensation for time and effort. The British National Health Service is increasingly integrating coproduction approaches into its health system—including but not limited to the mental health system—and could serve as a model 96–100 …”
Section: Potential Solutionsmentioning
confidence: 99%
“…The British National Health Service is increasingly integrating coproduction approaches into its health system-including but not limited to the mental health system-and could serve as a model. [96][97][98][99][100] Finally, social policy changes are critical to improving population mental health moving forward. 75 Specifically, the relationship between oppression and poor mental health points to the imperative to dismantle public policies that perpetuate oppression, such as mandatory minimum sentencing policies and funding of public education via property taxes.…”
Section: Potential Solutionsmentioning
confidence: 99%
“…5 More optimistically, however, there is emerging evidence to suggest successful change management following a renewed emphasis on PPIE: McLaughlin et al observed the importance of coproduction in improving chronic kidney disease care pathways in the NHS, while O'Flaherty et al also advocate for stakeholder engagement in evaluating the effectiveness of the NHS Health Check programme. 6,7 The implementation gap A key limitation when applying a systems approach to QI in healthcare has been to transition from a purely theoretical exercise towards real-world applicability. Despite being comprehensive in its scope, the approach is grounded in complexity and poses questions of resources, training and appetite.…”
Section: Benefitsmentioning
confidence: 99%